Antifungal and cytotoxic activities of selected medicinal plants from Malaysia - Chan, Yik Sin; Cheah, Yit Hong; Chong, Poh Zen; Khor, Hui Lai; Teh, Wen Siang; Khoo, Kong Soo; Ong, Hean Chooi; Sit, Nam Weng (Faculty of Pharmacy, University of Karachi, 2018)
This study was conducted to investigate the antifungal potential and cytotoxicity of selected medicinal plants from Malaysia. The extracts from the stem of Cissus quadrangularis and the leaves of Asplenium nidus, Pereskia bleo, Persicaria odorata and Sauropus androgynus were assayed against six fungi using p-iodonitrotetrazolium-based on colorimetric broth microdilution method. All the plant extracts were found to be fungicidal against at least one type of fungus. The strongest fungicidal activity (minimum fungicidal concentration=0.16 mg/mL) were exhibited by the hexane extract of C. quadrangularis, the hexane, chloroform, ethanol and methanol extracts of P. bleo, the hexane and ethyl acetate extracts of P. odorata, and the water extract of A. nidus. In terms of cytotoxicity on the African monkey kidney epithelial (Vero) cells, the chloroform extract of P. odorata produced the lowest 50% cytotoxic concentration (100.3 ± 4.2 μg/mL). In contrast, none of the water extracts from the studied plants caused significant toxicity on the cells. The water extract of A. nidus warrants further investigation since it showed the strongest fungicidal activity and the highest total activity (179.22 L/g) against Issatchenkia orientalis, and did not cause any toxicity to the Vero cells.